The Role of Outsourcing Leadership on Employee Performance at PT Titoh Wirapati Batam - Waruwu, Martonius; Nasruji (Journal of Management, 2024)
This study will look at how outsourced leadership, work motivation, and job satisfaction affect staff performance at PT Titoh Wirapati Batam. This study discovered that work motivation has a considerable beneficial effect on employee performance, with a significance level of 0.00. The T coefficient analysis yields a value of 3.330, which exceeds the T table value of 1.660, indicating that work motivation has a considerable impact on employee performance. Job happiness has no significant effect on employee performance (p-value = 0.482). The T coefficient analysis yields a value of 0.706, which is less than the T table value of 1.660, implying that work happiness has no meaningful impact on employee performance. Leadership style has a strong beneficial effect on employee performance (p-value=0.014). The T coefficient analysis yielded a value of 2.499, which is higher than the T table value of 1.660, indicating that leadership style has a considerable impact on employee performance. The F test findings demonstrate that the factors of work motivation, job satisfaction, and leadership style have a strong influence on employee performance, with a calculated F value of 24.953, which is higher than the F table value of 2.463. The R value of 0.662 implies that the variables collectively explain 66.2% of the variation in employee performance, with other factors accounting for 33.8%. In conclusion, this study emphasizes the importance of work motivation and leadership style in boosting employee performance, while job happiness has no significant impact.